Effect of Non-Dominant Resistance Training for Unilateral Athletes on Physical Balance and Isokinetic Muscular Function - Gyeo Rea Ui Bit Jung; Kyu Min Park; Sunghwun Kang (Asian Society of Kinesiology, 2019)
OBJECTIVES This study aimed investigates the effect of non-dominant resistance training on physical imbalance, and muscular function in unilateral athletes (badminton, tennis). METHODS Fifteen male unilateral sports plyer were randomly divided into non-dominant resistance training group (NRTG, n=8) and control group (CG, n=7). Exercise program performed for 60 min(warm-up 10 min, main exercise 40 min, cool down 10 min), three times a weeks. The isokinetic muscular function of knee and shoulder joint was measured pre (0 week) and post (8 weeks). RESULTS There was a significant different in isokinetic muscular function dominant and non-dominant (p<.05). Non-dominant resistance training program was effective in isokinetic muscular function (peak torque %BW, Total work %BW) in post- test than in pre-test (p<.05). And, was effective in improving shoulder joint isokinetic muscular function 600/sec, peak torque %BW (extension, flexion) in post- test than in pre-test (p<.05). In addition, knee isokinetic muscular function 1800/sec total work %BW (extension) the interaction effect was showed, and was effective 2400/sec total work %BW (flexor) (p<.05). CONCLUSIONS Non-dominant resistance training reduced right and left imbalances and improved isokinetic muscular function in unilateral athletes.